Factors associated with chronic kidney disease of non-traditional causes among children in Guatemala - Alejandro Cerón; Brooke M. Ramay; Luis Pablo Méndez-Alburez; Randall Lou-Meda (Pan American Health Organization, 2021)
Objective. To identify factors associated with chronic kidney disease of non-traditional causes among children in Guatemala. Methods. A cross-sectional survey was conducted. The study population was all pediatric patients with stage 5 chronic kidney disease active in FUNDANIER's pediatric nephrology unit (N = 156). Simple random sampling led to a total of 100 participants. Data collection consisted of a questionnaire addressing individual and household characteristics, access and utilization of health care, and place of residence when the disease began. Chronic kidney disease etiology was obtained from medical records. Municipality-level secondary data were collected. Descriptive statistics were estimated. Logistic regression was used for bivariate and multivariate analysis. Results. The odds ratio (OR) for almost all variables approached 1. Notable exceptions in household characteristics were mother's education level up to primary school (OR 2.2727) and living in an urban setting when symptoms began (OR 0.4035). Exceptions in municipal characteristics are zones with intensive small-scale agriculture (OR 3.8923) and those with intensive large-scale agriculture (OR 0.3338). P-values and confidence intervals show that the sample was not big enough to capture statistically significant associations between variables. Conclusions. Study findings suggest that factors associated with chronic kidney disease of non-traditional causes among children in Guatemala are intensive agricultural practices in their municipality of residence, and mother's level of education. Future research in children could use case-control designs or population-based studies in agricultural communities. Public health interventions that involve kidney function screening among children are recommended.